Plant-Based Diet Quality and Risk of Crohn's Disease and Ulcerative Colitis in US Women. (7th June 2021) - Wang, Fenglei; Baden, Megu; Li, Yanping; Hu, Frank; Willett, Walter; Khalili, Hamed; Ananthakrishnan, Ashwin; Chan, Andrew
Abstract: Objectives: Several plant-based foods have been associated with a lower risk of Crohn's disease (CD) and ulcerative colitis (UC), but not all plant-based foods are healthy. We aimed to examine the association of various plant-based diets with the risk of CD and UC. Methods: We followed 169 945 women in the Nurses' Health Study and Nurses' Health Study II for up to 32 years. Plant-based diets were assessed by three indices derived from the food frequency questionnaires: an overall plant-based diet index (PDI), a healthful plant-based diet index (hPDI), and an unhealthful plant-based diet index (uPDI). Self-reported CD and UC were confirmed through medical record review. Results: We documented 320 incident CD cases and 404 incident UC cases during 4 317 561 person-years. A higher hPDI was associated with a lower risk of UC (hazard ratio [HR] comparing extreme quintiles: 0.67; 95% confidence interval [CI]: 0.47–0.94; P-trend = 0.02). In contrast, the uPDI was associated with an increased risk of CD (HR: 1.67; 95% CI: 1.11–2.51; P-trend = 0.002) and UC (HR: 1.65; 95% CI: 1.15–2.35; P-trend = 0.03). Replacing refined grains, sugar-sweetened beverages, and sweets/desserts with an equal serving of fruits or vegetables was associated with lower risk of CD and UC. Conclusions: A healthful plant-based diet rich in fruits and vegetables was associated with a lower UC risk, whereas a plant-based diet emphasizing less healthy plant foods such as refined grains, sugar-sweetened beverages, and sweets/desserts was associated with a higher CD and UC risk. Funding Sources: National Institutes of Health.